Belowground Interspecies Interaction Enhances Productivity and Water Use Efficiency in Maize–Pea Intercropping Systems. Issue 1 (1st January 2015) - Chen, Guodong; Chai, Qiang; Huang, Gaobao; Yu, Aizhong; Feng, Fuxue; Mu, Yanping; Kong, Xuefu; Huang, Peng
ABSTRACT: Intercropping is shown to have yield advantages compared with sole cropping, but it is unknown how much yield advantage is due to belowground interspecies interactions. Here we determined grain yield, land equivalent ratio (LER), and water use efficiency (WUE) of maize ( Zea mays L.)–pea ( Pisum sativum L.) intercropping and quantified the magnitude of the contribution by belowground interspecies interactions. Field experiments were conducted at Wuwei (37°96′ N, 102°64′ E), northwest China, in 2009 and 2010. Treatments included sole maize, sole pea, and three maize–pea intercropping systems that, respectively, had no root‐barrier (M–P), plastic sheet barrier (PM–P), and nylon mesh barrier (NM–P). The plastic sheet and nylon mesh barriers were vertically placed to 1‐m deep between the two intercrop strips; this allowed the quantification of belowground interspecies interactions. On a per hectare basis, the maize–pea intercropping increased grain yields by an average of 31.3% and improved WUE by 21.9% compared with the corresponding sole maize and sole pea. The LER value was 1.33 for the M–P system, suggesting that the grain yield produced by the maize–pea intercrops per hectare is equivalent to the yield that sole crops would produce with 33% additional farmland. The M–P system had the yield of 11, 034 kg ha −1, which was 21.9% greater compared with the PM–P system and 9.7% greater compared with the NM–P system. The comparison of the three intercropping systems revealed that belowground interspecies interactions contributed 59.3% of the increased yields and 88.9% of the improved WUE. Of the increased yield, about 40% was due to water movement between the two strips and the remaining 19% was due to root overlapping activity. We conclude that sharing resources in the rooting zones between the intercrops serve as a major mechanism responsible for the large yield and WUE advantages for the maize–pea intercropping in arid areas.